2010
DOI: 10.1051/0004-6361/201014133
|View full text |Cite
|
Sign up to set email alerts
|

VLBI observations of SN 2008iz

Abstract: We present observations of the recently discovered supernova 2008iz in M 82 with the VLBI High Sensitivity Array at 22 GHz, the Very Large Array at frequencies of 1. 4, 4.8, 8.4, 22 and 43 GHz, and the Chandra X-ray observatory. The supernova was clearly detected in two VLBI images separated by 11 months. The source shows a ring-like morphology and expands with a velocity of ∼23 000 km s −1 . The most likely explosion date is in mid-February 2008. The measured expansion speed is a factor of ∼2 higher than exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 40 publications
3
50
0
Order By: Relevance
“…Its CCSN rate is estimated to be ∼ð2.1 − 20Þ × 10 −2 CCSNe yr −1 [118,119]. The most recent CCSN in M82 was SN2008iz, a Type II SN first observed on May 3, 2008 [120].…”
Section: A Location Of Snementioning
confidence: 99%
“…Its CCSN rate is estimated to be ∼ð2.1 − 20Þ × 10 −2 CCSNe yr −1 [118,119]. The most recent CCSN in M82 was SN2008iz, a Type II SN first observed on May 3, 2008 [120].…”
Section: A Location Of Snementioning
confidence: 99%
“…A fraction of supernovae, however, will be missed in optical surveys due to strong dust extinction. Indeed, a supernova SN 2008iz in M82 is discovered only in the radio bands (Brunthaler et al 2009(Brunthaler et al , 2010. Even if associated supernovae are not identifiable, they can be distinguished from merger events using timescale arguments, which are significantly longer than those of GW-radio counterparts, and radio spectral properties.…”
Section: False Positives: Extragalactic Radio Transients and Variablesmentioning
confidence: 99%
“…Radio very long baseline interferometry studies of the innermost regions of LIRGs have, in fact, revealed scores of radio SNe and supernova (SN) remnants that have remained hidden at other wavelengths (Lonsdale et al 2006;Pérez-Torres et al 2009;Ulvestad 2009;Bondi et al 2012;Herrero-Illana et al 2012;Romero-Cañizales et al 2012). A few bona fide radio transients have also been identified as obscured SNeII, e.g., an SN in the starburst Galaxy Mrk297 (Yin & Heeschen 1991), VLA 121550.2+130654 (Gal-Yam et al 2006), and SN2008iz in M82 (A V > 10 mag ;Brunthaler et al 2009Brunthaler et al , 2010Mattila et al 2013).…”
Section: Introductionmentioning
confidence: 99%